Enhancing Environmental DNA Sampling Efficiency for Cetacean Detection on Whale Watching Tours - Lauren Kelly Rodriguez; Belén García Ovide; Eleonora Barbaccia; Jana Robertson; Taïme Smit Pellure; Ángela Ceballos‐Caro; Caterina Lanfredi; Maddalena Jahoda; Enrico Villa; Arianna Azzellino; Marianne Helene Rasmussen; Michael Traugott; et al. (Environmental DNA)
ABSTRACT Monitoring cetaceans is essential for evaluating ecosystem health and informing the establishment of marine protected areas. Conventional cetacean monitoring techniques, such as photo‐identification, acoustic surveys, and satellite tagging, are often resource‐intensive, costly, and sometimes intrusive. Environmental DNA (eDNA)‐based methods have emerged as non‐invasive, cost‐efficient complements based on the analysis of genetic material shed into the environment. However, eDNA research is still evolving, with ongoing efforts to optimize field sampling and laboratory protocols. Building on the challenges of conventional monitoring methods, this study sought to refine eDNA sampling parameters to offer a more efficient and scalable approach for cetacean research, leveraging citizen science platforms. From June to October 2023, eDNA samples were collected across three regions in the Northeast Atlantic Ocean and Mediterranean Sea aboard whale‐watching vessels or monitoring platforms engaging citizen scientists. Samples were analyzed for total DNA concentration using Qubit fluorometry and target DNA concentration with quantitative polymerase chain reactions (qPCR). Key variables tested in the field included water volume (2, 5, and 10 L), sampling timing (immediately after a whale was present and at 5‐, 10‐, and 20‐min intervals), and three filter types (pore sizes of 1.2, 0.8, and 0.45 μm). Our results illustrate that larger water volumes (10 L), sampling immediately after a whale breach or fluking behavior, and Smith‐Root eDNA filters (1.2 μm pore size) significantly increased eDNA detection probability and signal strength. However, the combination of certain filter types with different water volumes had a significant impact on detection probability, with smaller pore sizes more effectively yielding detections with a lower water volume. These findings provide guidance for future cetacean research initiatives and highlight the potential of eDNA methods in enhancing research and conservation efforts through scalable citizen science‐based initiatives.